Ultralight biomass-derived carbon fibre aerogels for electromagnetic and acoustic noise mitigation. Issue 42 (19th October 2022) - Hou, Yi; Quan, Jing; Thai, Ba Quoc; Zhao, Yijing; Lan, Xiaoling; Yu, Xiang; Zhai, Wei; Yang, Yong; Khoo, Boo Cheong
Abstract : The silkworm derived carbon fibre aerogel (SA) could be a promising building material to address the ever-growing noise (EM and sound) issues and improve the energy efficiency of the architectures. Abstract : The ever-increasing electromagnetic (EM) noise and acoustic noise are threatening public health in modern cities. Though materials are being developed, there is a lack of simple solution to address these two types of noise at the same time. Herein, flexible and ultralight (∼15 mg cm −3 ) silk fibre derived carbon fibre aerogels (SAs) are developed. The silk fibre mats, carbonized at different temperatures, are stacked together to form a compressible multi-layer structure. With optimized gradient impedance, the SA could achieve low-reflection coefficient ( R < 0.02) electromagnetic interference (EMI) shielding in X and Ku bands (8.2 to 18 GHz). Moreover, the SA demonstrates an outstanding sound absorption performance (average absorption coefficient > 90%) from 1000 to 6000 Hz. Besides, the aerogel also shows a low thermal conductivity of ∼0.026 Wm −1 K −1, implying a potential thermal insulator. With such excellent performance and facile fabrication, the SA is expected to serve as a promising building material to be applied on the surface of architectures for the demand of both noise mitigation as well as energy conservation. The strategy to achieve multiple functions by using a multi-layered fibrous aerogel could also be applied to other natural fibres.